Efectividad del programa educativo capacitando al cuidador del adulto mayor dependiente sobre cuidados básicos en el centro poblado Chequen, 2010 - Alva Chuquilin, Angela Dryedi (2010)
This type of research study is pre-experimental and design and contrasting on pre and post test, was held in the town of Chequen during the months of December 2009 to March 2010, In order to determine the effectiveness of the educational program in the caregiver's knowledge level of dependent elderly. The sample consisted of 40 caregivers, who were assigned at random, and that formed the experimental group. To obtain the data were used as instruments: a format pre test and post test about the levels of knowledge of caregivers on basic care for the dependent elderly, 20 questions consisting of valid and reliable, applied considering the rights of anonymity, free participation and confidentiality. The Data processing was performed using SPSS for Windows version 15. The results are presented in frequency tables absolute and relative percentage. Tables also report standard deviations average scores achieved by family caregivers of dependent elderly in the relevant instruments. The statistical analysis reported the effectiveness of the educational program, analyzed with the t-student test for comparison of means for independent and related samples to examine changes before and after implementing the program, with a statistical significance level of 5% probability.